Aankopen 1978-1982. - Paalman, Hans (Schiedam : Stedelijk Museum Schiedam, 1983)
Armando ; Bagman, Herman ; Doiz, Dora ; Ebbinge, Ineke ; Gelder, Ton van ; Geurts, Joris ; Haastert, Inge van ; Keijser, Ad de ; Koningsbruggen, Rob van ; Rubens, Albert ; Vandenbranden, Guy ; Berkulin, Arie ; Brasser, Fons ; Henderickx, Sjef ; Klapwijk, Peter ; Struycken, Peter ; van Amen, Woody ; Baljeu, Joost ; Cassée, Dick ; Haas, Aad de ; Kuypers, Theo ; etc.
Aankopen 1978-1982, Stedelijk Museum Schiedam, 17 februari - 14 maart 1983
boek